2021
DOI: 10.3389/fmicb.2021.663757
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching and Electrochemical Behavior of Chalcopyrite by a Mixed Culture at Low Temperature

Abstract: Low-temperature biohydrometallurgy is implicated in metal recovery in alpine mining areas, but bioleaching using microbial consortia at temperatures <10°C was scarcely discussed. To this end, a mixed culture was used for chalcopyrite bioleaching at 6°C. The mixed culture resulted in a higher copper leaching rate than the pure culture of Acidithiobacillus ferrivorans strain YL15. High-throughput sequencing technology showed that Acidithiobacillus spp. and Sulfobacillus spp. were the mixed culture’s major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
0
2
0
2
Order By: Relevance
“…Biomining and bioleaching of valuable metals from mineral raw materials are combined chemical and biological processes in which microorganisms are used in catalyzing the metal oxidation and to change the structure of the treated minerals, change the pH and redox in the medium, and to destroy refractory ores. The economic limitations of biomining for metal recovery are inefficient productivity at low temperatures [ 102 ] and the need for the additional biomass preparation. At the same time, the use of microorganisms in hydrometallurgy is expedient in warm climatic zones and during warm season in a moderate climate.…”
Section: Discussionmentioning
confidence: 99%
“…Biomining and bioleaching of valuable metals from mineral raw materials are combined chemical and biological processes in which microorganisms are used in catalyzing the metal oxidation and to change the structure of the treated minerals, change the pH and redox in the medium, and to destroy refractory ores. The economic limitations of biomining for metal recovery are inefficient productivity at low temperatures [ 102 ] and the need for the additional biomass preparation. At the same time, the use of microorganisms in hydrometallurgy is expedient in warm climatic zones and during warm season in a moderate climate.…”
Section: Discussionmentioning
confidence: 99%
“…Los seis CMPL formados principalmente por ambos géneros, presentaron crecimiento y lixiviaron sulfuro de cobre a una temperatura de 15 °C, permitiendo la recuperación de cobre de hasta el 12.47%. Después de 30 a 35 días de evaluación, los CMPL alcanzaron concentraciones entre 2.3 x10 8 y 2.8 x10 8 células/mL, valores cercanos a lo obtenido por el consorcio MHJ evaluado por Peng et al (2021) para la biolixiviación de calcopirita a 6 °C. Estos consorcios, conformados principalmente por Acidithiobacillus spp.…”
Section: Discussionunclassified
“…Con respecto a los trabajos anteriores, han enfatizado la importancia de las interacciones mutualistas entre microorganismos acidófilos autótrofos y heterótrofos para mejorar la disolución de minerales de sulfuro (Okibe & Johnson 2004;Peng et al 2021). Los consorcios conformados por Acidiphilium, Acidithiobacillus y Leptospirillum, son empleados generalmente a condiciones mesofílicas y/o termofílicas.…”
Section: Discussionunclassified
“…that outcompeted At. ferrivorans strain YL15 at 6°C (Peng et al, 2021 ). Finally, the accumulation of solid sulfur during chalcopyrite bioleaching was observed that was explained by decreased gene expression of genes coding for ISC oxidation in At.…”
Section: Biotechnologymentioning
confidence: 99%